PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Aisyah Mentari W, 11.05.52.0127; Aini, Nur (Students Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the effect of Intellectual Capital to Profitability. Intellectual capital consisting of Value Added Human Capital (VAHU), Structural Capital Value Added (STVA), and Value Added Capital Employed (VACA) using model Pulic - Value Added Intellectual Coefficients (VAICTM). Profitability is proxied by Return on Assets (ROA). The population in this study are all commercial banks listed on the Indonesia Stock Exchange (BEI) 2012-2014. The sample was banking companies listed in Indonesia Stock Exchange in 2012-2014. Based on the purposive sampling method, samples obtained 27 companies. This study used multiple linear regression to analyze the data. Based on the results of hypothesis testing, it is known that the value added of human capital and structural capital value added does not affect the profitability of the banks that went public on the Indonesian Stock Exchange. Value added capital employed positive effect on the companys profitability in the bank to go public in Indonesia Stock Exchange.Keywords: Intellectual Capital, VAHU, STVA, VACA and Profitability